Marketing Communication Strategis Through Social Media Instagram (Case Study @ntvnews.id) - Fiqih Akhdiyatu Salam; Nurtjahyadi; Prehapsari Julia Majid; Weni Novita (CV. ITTC INDONESIA, 2024)
This research aims to analyze the marketing communication strategies implemented by online news media NTvnews.id through the social media platform Instagram, utilizing the Integrated Marketing Communication (IMC) 7P theory. The research method employed is qualitative, with data collection techniques involving in-depth interviews, participant observation, and document analysis. The research findings reveal that NTvnews.id utilizes integrated marketing communication strategies across various social media platforms, particularly Instagram. The research findings demonstrate that NTvnews.id has successfully implemented effective marketing communication strategies through social media, particularly Instagram. This is evidenced by the significant increase in followers, likes, comments, and shares. This research contributes significantly to the comprehension of marketing communication strategies employed by online news media in the digital age.